IoT based parking system: prospects, challenges, and beyond - Quader, Shafquat Mahmud; Nova, Salma Hani; Talukdar, Saumitra Das; Sayeed, Md.Shaba; Sadab, Mubtasimur Rahman (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.